Estudo das linhas de pedra na Serra do Tepequém em Amajarí-RR - Rodrigues, Sheilly Miranda (2017)
In the north of the state of Roraima, in the municipality of Amajarí stands out in the Serra do Tepequém, this one was carved in the sediments of the Tepequém Formation, Paleoproterozoic age, consisting of conglomerates, sandstones, siltstones, argillites. In the interior portion of the mountain range, a planar intravale plain is identified, which Is under strong erosive linear-gauge action. The plains are surrounded by hills and hills that present at the base of their slopes deposits The colluvial/ pedunized aluos forming inconsistent soils with the presence of lines of stones. The present research aims to understand the evolution of the landscape of the Tepequém mountain range, based on the analysis of the stone lines. Two fieldwork steps were carried out and the activities were carried out Identification of the spatial distribution of stone lines, morphometric data were acquired considering the following parameters Width, arrangement, shape, extent, thickness, profile location and acquisition of UTM coordinates through GPS. After that, 16 samples of sediments / soils and pebbles of the stone lines were collected, being deposited in plastic bags and identified for later laboratory analysis. In the laboratory, digital images were manipulated and manipulated to create thematic maps, as well as spatial map and map of the Geomorphological Compartment of the mountain range. The sediments were submitted to granulometric, mineralogical, morphological and chemical analyzes. At the top of the mountain range of Tepequém, the stone lines are concentrated in the intermontanas plains, secondarily at the base of the hills and hills. The stone lines are positioned horizontally to the surface of the terrain, being common in the plains in a continuous and discontinuous way and positioned subhorizontally continuously in the low slope of hills. The soils and the sediment / matrix of the stone lines present granulometry by sandy fraction and silica sand, with a predominance of fine sand and silt texture, highly acidic and poor in organic matter, are poorly selected, with a degree of negative asymmetry Positive, and values of kurtosis in platicúrtica to very leptocúrtica. The grains of the sediments and pebbles that make up the stone lines have subangled to round morphology. They consist predominantly of quartz, still containing muscovite and kaolinite, and in smaller amount hematite, goethite and ilmenite present in the stone lines. Soils on average were more alkaline than ferruginous. They are silica-aluminosos, due to the great abundance of quartz. Therefore, the stone lines are indicative of the evolution of the landscape, marked by long dry periods and short humid periods, Corresponding to old deposits of coarse fragments associated with mechanical morphogenesis, promoted by the climatic oscillations.